Student Readiness in Mathematics in The New School Year 2024-2025 - SHANDY, Aries Nur (Journal of Social Sciences and Cultural Study, 2024)
This research examined the factors affecting students' readiness to study mathematics at the beginning of the 2024–2025 academic year. The study was carried out at MA Husnul Khotmah Kuningan. The sampling method used in this research was purposive sampling. The research employed a qualitative method with a case study model. Data collection instruments included questionnaires, interviews, and observations. The study results indicated that the factors with the highest percentages were cooperation among students, learning facilities, parental support, and the quality of teaching, which played a significant role in creating a supportive and effective learning environment. Indicators with the highest values highlight factors that profoundly and directly influence students' learning readiness. Factors such as student cooperation, learning facilities, parental support, and teaching quality significantly create a supportive and effective learning environment. While factors with lower percentage values, such as study habits and additional activities, are also important, they may require further attention to enhance overall learning readiness. Understanding and improving all these factors can help create a better learning environment and prepare students to face academic challenges.